Causal association between tea intake and risk for gout: a Mendelian randomization study - Liang, Xiao; Cai, Jingjing; Fan, Yuchao (Frontiers in Genetics, 2023)
Background: Gout, an increasingly prevalent form of inflammatory arthritis, is caused by the accumulation of uric acid crystals in joints, resulting in severe pain, swelling and stiffness that adversely affect physical, mental and emotional well-being. The management of gout requires a combination of medication and lifestyle modifications. Recent studies suggest that tea intake may reduce the risk of developing gout; however, further research is needed to establish a causal relationship. Methods: In this study, we employed a bidirectional two-sample Mendelian randomization (MR) approach, utilizing genome-wide association study (GWAS) summary statistics, to investigate the causal association between increased tea intake and gout. We meticulously selected instrumental variables (IVs) based on rigorous criteria and employed five different MR methods. Heterogeneity was assessed using Cochran's Q statistic, and pleiotropy was evaluated using the MR Egger intercept and MR-PRESSO tests. Weak IVs were identified using F values. The Phenoscanner database was consulted to exclude single nucleotide polymorphisms associated with confounding factors or outcomes. Results: The study included one dataset related to tea intake (ukb-b-6066) and three datasets related to gout (ukb-b-12765, finn-b-M13_GOUT, and finn-b-GOUT_STRICT). Our forward MR analysis suggest a causal relationship between increased tea intake and reduced risk of gout in all three gout-related datasets (OR [95% CI]: 0.9966[0.9938 - 0.9993], p =0.0167; 0.4842 [0.2683 - 0.8737], p-value = 0.0160; and 0.4554[0.2155 - 0.9623], p = 0.0393, respectively). The reveres MR showed increased risk of gout (ukb-b-12765) was significantly associated with low tea intake according to the IVW analysis (OR [95% CI]: 0.0062[0.0002 - 0.154], p = 0.0020). However, this association was not observed in the Finn-b-M13_GOUT and Finn-b-GOUT_STRICT (OR [95% CI]: 0.9992[0.9909 - 1.0075], p = 0.8453 and OR [95% CI]: 0.9996[0.9932 - 1.0059], p = 0.8896, respectively). No significant heterogeneity or potential pleiotropy was detected, and the possibility of weak IVs was also excluded. Conclusion: Our MR analysis suggest a causal relationship between genetically predicted tea intake and a decreased risk of gout. These findings underscore the potential advantages of increasing tea intake for preventing gout. However, further research is needed to validate these results and elucidate the underlying mechanisms.